The Demonstration Method: Enhancing Learning Outcomes in the Creation of Gorga Motif Batik - Muhammad Hasyim Azhari; Daulat Saragi (Gorga : Jurnal Seni Rupa, 2026)
This study aims to improve learning outcomes of Gorga-patterned batik crafts through the application of the demonstration method to class XI students of SMA Negeri 1 Batang Kuis using the Classroom Action Research (CAR) approach, which is implemented through the stages of planning, action, observation, and reflection. The object of the study was all class XI students, while the subject of the study was class XI E, totaling 33 students selected using a simple random sampling technique. The demonstration method was chosen because it is able to provide concrete understanding by directly showing the process, steps, and techniques of batik, so that students can more easily imitate and practice them. The research instrument was a learning outcome test in the form of Gorga-patterned batik works carried out through pre-test and post-test. The score needed to achieve completeness is >78.  The results of the study showed that the average class score in the pre-test stage was 76, which means that they had not yet achieved learning mastery. After the implementation of the demonstration method, the average class score increased to 83.45 or an increase of 9.80%, with all students (100%) achieving learning mastery. Of these, 8 students (18.18%) obtained the excellent category (A) and 25 students (81.81%) obtained the good category (B). Thus, it can be concluded that the demonstration method is effective in improving student learning outcomes in making Gorga motif batik. This study also recommends that art and culture teachers apply the demonstration method not only to improve learning outcomes, but also as an effort to preserve local culture through batik craft learning in schools.